A laterally π-expanded fluorone dye as an efficient near infrared fluorophore. Issue 27 (3rd March 2016) - Sezukuri, Kyohei; Suzuki, Mitsuharu; Hayashi, Hironobu; Kuzuhara, Daiki; Aratani, Naoki; Yamada, Hiroko
Abstract : FBX in DMSO displays remarkably red-shifted and sharp absorption and fluorescence bands at 817 nm and 853 nm, respectively. Abstract : The synthesis and photophysical properties of new dibenzo[ b, i ]fluorone dye frameworks (BX and FBX) are described. Both BX and FBX display near-infrared sharp absorption and emission upon the addition of base due to the achievement of efficient π-conjugation based on the small bond alternation strategy.